Dioxin-like activities in serum across European and Inuit populations. - LONG M; ANDERSEN BS; LINDH CH; HAGMAR L; GIWERCMAN A; MANICARDI, Gian Carlo; BIZZARO D; SPAN M; TOFT G; PEDERSEN HS; ZVYEZDAY V; BONDE JP; et al. (Environmental Health, 2006)
Persistent organic pollutants (POPs) such as polychlorinated dibenzo-p-dioxins/furans, polychlorinated biphenyls (PCBs) and organochlorine pesticides can cause a series of adverse effects on e.g. reproduction in animals and humans, many of which involve the aryl hydrocarbon receptor (AhR). The aim of the present study was to compare the integrated serum level of AhR mediated activity among European and Inuit populations, and evaluate whether the activity was associated to the selected POP markers, 2,2',4,4',5,5'-hexachlorobiphenyl (CB-153) and 1,1-dichloro-2,2-bis(p-chlorophenyl)-ethylene (p,p'-DDE).